Powering the Future Smart Mobility: A European Perspective on Battery Storage - Natascia Andrenacci; Francesco Vitiello; Chiara Boccaletti; Francesco Vellucci (Batteries)
Batteries are central to the global energy system and fundamental elements for energy transition and future mobility. In particular, the growth in electric vehicle (EV) sales is pushing up demand for batteries. Most of the battery demand for EVs today can be met with domestic or regional production in China, while the share of imports remains relatively large in Europe and the United States. Boosting the industrial base for battery production is therefore a key task for the EU. To make its battery supply chains secure, resilient, and sustainable, the EU’s approach consists of improving cooperation among stakeholders, providing the sector with funding, and establishing a comprehensive regulatory framework. In this paper, an accurate review of the state-of-the-art of automotive batteries is provided, including the performance, safety, sustainability, and costs of the different battery technologies. The significant challenges the EU battery sector must face, such as dependencies on third countries and high energy and labor costs, are discussed. An overview of the present European regulation and of future trends is provided.